2010
DOI: 10.1590/s1806-83242010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal alterations among the institutionalized elderly in Brazil

Abstract: This study determined the prevalence of oral mucosal alterations and associated factors among the institutionalized elderly in Brazil. Data were collected through a structured questionnaire, a review of their medical records and an intra-oral examination. A sample of 335 individuals over 60 years of age was randomly selected. In total, 646 alterations were diagnosed; 59.1% were variations of the normal oral mucosa. The most frequent variation consisted of sublingual varicosities (51.6%). Denture stomatitis (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
37
8
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 24 publications
11
37
8
11
Order By: Relevance
“…However, the wide variety of oral mucosa alterations identified in this study is consistent with the findings of other reports. [4][5][6][7]10,12,14 Of the 511 patients enrolled in this study, 71.8% (n = 367) were female. This overrepresentation of female patients has also been observed in other epidemiological studies of the prevalence of oral mucosa alterations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the wide variety of oral mucosa alterations identified in this study is consistent with the findings of other reports. [4][5][6][7]10,12,14 Of the 511 patients enrolled in this study, 71.8% (n = 367) were female. This overrepresentation of female patients has also been observed in other epidemiological studies of the prevalence of oral mucosa alterations.…”
Section: Discussionmentioning
confidence: 99%
“…This overrepresentation of female patients has also been observed in other epidemiological studies of the prevalence of oral mucosa alterations. 5,10,13,14 It is possible that this observation reflects a greater concern about oral health among women than among men. 11,19 The prevalence of oral mucosa alterations found in this study was higher (84.9%) than in similar studies in Spain 7 (51.9%) and Turkey 10 (41.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferreira et al 22 reported a highly significant association between the failure of a patient to remove his/her dentures before sleep and the development of disease. These data are consistent with our findings that wearing dentures while sleeping promotes disease onset (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The iatrogenesis happens also due to the fact that many prostheses are made by professionals who aren't able to make them. In a study with elderly who used removable prosthesis, 54.2% reported that the prostheses weren't made by dentistsurgeons, harming the stomatognathic system because of unsatisfactory removable prostheses, causing pain, problem in use, discomfort and oral lesions 13,14 .…”
Section: Introductionmentioning
confidence: 99%